Dr. Tom Shinder's ISA server 2006 migration guide - Shinder, Thomas W.; Shinder, Debra Littlejohn; Dimcev, Adrian F. (Syngress Pub., 2007)
Dr. Tom Shinder's first 2 books on configuring ISA Server have sold more than 50,000 units worldwide!
Keywords: Microsoft ISA server; Firewalls (Computer security); Internet -- Security measures; Systems migration; Coupe-feu (Sécurité informatique); Internet; Sécurité; Mesures; Migration (Informatique); COMPUTERS; Reference; COMPUTERS; Machine Theory; COMPUTERS; Computer Literacy; COMPUTERS; Information Technology; COMPUTERS; Data Processing; COMPUTERS; Computer Science; COMPUTERS; Hardware; General; Internet; Security measures